Inter-cultural dialogue as a means of reflecting the author’s standpoint in the story Merry Gertrude by Y. Buyda - Prokhorova, Tatyana (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
The essay based on the analysis of the story Merry Gertrude by contemporary author Y. Buyda addresses the forms and functions of inter-cultural dialogue as a means of reflections of the author's standpoint.